2016
DOI: 10.1002/aic.15541
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric charging of monodisperse particles in fluidized beds

Abstract: To investigate the interplay between particle charging and hydrodynamics in fluidized beds, models for triboelectric charging and electrostatic forces were built into a computational fluid dynamics‐discrete element method model. Charge transfer was governed by the difference in effective work function between contacting materials as well as the electric field at the point of contact. Monodisperse particles were fluidized with an effective work function difference between the particles and the conducting walls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 61 publications
3
51
0
Order By: Relevance
“…This increases the average contact area and hence the average charge transferred in each collision. Based on the soft-sphere contact model, Kolehmainen et al (2017a) concluded that if damping forces are neglected, the ratio of the charge that would be transferred in a real contact to the charge transferred in a simulated 'soft' contact is…”
Section: Numerical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…This increases the average contact area and hence the average charge transferred in each collision. Based on the soft-sphere contact model, Kolehmainen et al (2017a) concluded that if damping forces are neglected, the ratio of the charge that would be transferred in a real contact to the charge transferred in a simulated 'soft' contact is…”
Section: Numerical Modelmentioning
confidence: 99%
“…A list of so-called interacting cells is constructed at the beginning of the simulations to track the location of the particles in the computational mesh. The short-range term is not limited by a prescribed cutoff radius as in Kolehmainen et al (2016Kolehmainen et al ( , 2017a but covers all the particles located in the interacting cells. The list of interacting cells is determined according to the desired minimum distance of the short-range term (δ s,min ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It does not describe the microscopic chemistry or physics of how charges rearrange to produce the phenomenological behaviors defined by Eq's [1] and [2]. Several groups have published important contributions, for example dealing with changes to effective material work functions due to the fields produced by charged particles 11,12,13 , and with carriers that may be responsible for surface charge transport 14,15 . Second, the change in polarization on a particle inevitably feeds back on itself -i.e.…”
Section: (D)mentioning
confidence: 99%